Parallel single‐cell optical transit dielectrophoresis cytometer. Issue 9 (19th February 2020) - Fazelkhah, Azita; Afshar, Samaneh; Durham, Nicholas; Butler, Michael; Salimi, Elham; Bridges, Greg; Thomson, Douglas
Abstract: In this work, we present an optical transit DEP flow cytometer for parallel single‐cell analysis. Each cell's dielectric property is inferred from velocity perturbations due to DEP actuation in a microfluidic channel. Dual LED sources facilitate velocity measurement by producing two transit shadows for each cell passing through the channel. These shadows are detected using a 256‐pixel linear optical array detector. Massively parallel analysis is possible as each pixel of the detector can independently analyze the passing cells. A wide channel (∼18 mm) was employed to carry many particles simultaneously, and the system was capable of detecting the velocity of over 200 cells simultaneously. We have achieved analysis rates for 10 µm diameter polystyrene spheres response exceeding 250 per second. With appropriate calibration, this DEP cytometer can quantitatively measure the dielectric response. The dielectric response (Clausius–Mossotti factor) of viable CHO cells was measured over the frequency range of 100 kHz to 6 MHz, and the obtained response matches the previously measured values by our group. The DEP cytometer uses simple modular components to achieve high throughput label‐free single‐cell dielectric analysis and can begin analyzing particles within 10 s after starting to pump the sample into the channel.